2023
DOI: 10.3389/fpsyg.2023.1226703
|View full text |Cite
|
Sign up to set email alerts
|

The resilience of emergency and critical care nurses: a qualitative systematic review and meta-synthesis

Shuyang Liu,
Yu Zhang,
Yue Liu
et al.

Abstract: BackgroundDue to the unique work environment, emergency and critical care departments nurses face high job pressure, often resulting in burnout and a high turnover rate. Public health emergencies such as the Corona Virus Disease 2019 pandemic tend to exacerbate these problems further. Therefore, improving the resilience of nurses is crucial to enhance their retention rates.ObjectiveThis systematic review and meta-synthesis of qualitative studies on the resilience of emergency and critical nurses were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…This aligns with our earlier observation regarding the association between poor health and increased burnout risk. Furthermore, job-related stress was identified as a burnout risk, echoing another study’s findings [ 39 ]. Interestingly, a prior study demonstrated that health-related quality of life, another measure of personal health, exhibited a strong correlation with burnout [ 40 ].…”
Section: Discussionsupporting
confidence: 66%
“…This aligns with our earlier observation regarding the association between poor health and increased burnout risk. Furthermore, job-related stress was identified as a burnout risk, echoing another study’s findings [ 39 ]. Interestingly, a prior study demonstrated that health-related quality of life, another measure of personal health, exhibited a strong correlation with burnout [ 40 ].…”
Section: Discussionsupporting
confidence: 66%